Design and test of gravity self balancing upper limb rehabilitation robots - MA Chong; LI Shouzhong; KUANG Xinyu; ZHANG Wenlong; LI Junli; ZHAO Hongzhe (Jixie chuandong)
ObjectiveAdding a gravity balance mechanism to robots can effectively improve their dynamic performance.However, there are few existing upper limb rehabilitation training robots that involve end traction balance mechanisms. Based on the analysis of the change law of the center of mass during the cantilever working process of the upper limb rehabilitation robot, a cantilever mechanism of the upper limb rehabilitation robot that can automatically balance gravity was designed to address this issue.MethodsThis institution can achieve gravity balance by determining the position and parameters of the zero length spring, which means that only one spring is needed to meet the self balance of the upper limb rehabilitation robot cantilever in tension and rotation working states. In theory, joint loads generated by gravity can be completely eliminated, energy loss can be reduced, and the working range and system performance of upper limb rehabilitation robots can be improved. And a rehabilitation robot balance model was designed and a prototype test platform was built to verify the accuracy of the model and the feasibility of the design scheme.ResultsThe results show that compared with the traditional traction rehabilitation cantilever, the balance effect of spring gravity balance scheme is significant, the torque required for balance is reduced by 92%, and the joint driving torque is reduced by 85%.